Polymorphisms in Processing and Antigen Presentation-Related Genes and Their Association with Host Susceptibility to Influenza A/H1N1 2009 Pandemic in a Mexican Mestizo Population - Marco Antonio Ponce-Gallegos; Aseneth Ruiz-Celis; Enrique Ambrocio-Ortiz; Gloria Pérez-Rubio; Alejandra Ramírez-Venegas; Nora E. Bautista-Félix; Ramcés Falfán-Valencia (Viruses, 2020)
(1) Background: The influenza A/H1N1 pdm09 virus rapidly spread throughout the world. Despite the inflammatory and virus-degradation pathways described in the pathogenesis of influenza A virus (IAV) infection, little is known about the role of the single nucleotide polymorphisms (SNPs) in the genes involved in the processing and antigenic presentation-related mechanisms. (2) Methods: In this case-control study, we evaluated 17 SNPs in five genes (TAP1, TAP2, TAPBP, PSMB8, and PSMB9). One hundred and twenty-eight patients with influenza A/H1N1 infection (INF-P) and 111 healthy contacts (HC) were included; all of them are Mexican mestizo. (3) Results: In allele and genotype comparison, the rs241433/C allele (TAP2), as well as AG haplotype (rs3763365 and rs4148882), are associated with reduced risk for influenza A/H1N1 infection (p < 0.05). On the other hand, the rs2071888G allele (TAPBP) and GG haplotype (rs3763365 and rs9276810) are associated with a higher risk for influenza A/H1N1 infection. In addition, after adjustment for covariates, the association to a reduced risk for influenza A/H1N1 infection remains with rs241433/C allele (p < 0.0001, OR = 0.24, 95% CI = 0.13–0.43), and the association with TAPBP is also maintained with the G allele (p = 0.0095, OR = 1.89, 95% CI = 1.17–3.06) and GG genotype models (p < 0.05, OR = 2.18, 95% CI = 1.27–3.74). (4) Conclusion: The rs241433/C allele and AC genotype (TAP2) and the AG haplotype are associated with a reduced risk for influenza A/H1N1 infection. In addition, the rs2071888/G allele and GG genotype (TAPBP) and the GG haplotype are associated with a higher risk for developing influenza A/H1N1 infection in a Mexican mestizo population.